Optimized design of water-saving system in-slab cooling plant of Mobarakeh steel complex. (10th February 2022) - Beni, Mahdi Hashemi; Bazofti, Milad Morad; Golkar, Babak; Saboohi, Yadollah; Mokhtari, Hamid; Milani, Bahar
Abstract: The aim of this paper is to provide a solution to decrease water consumption in the slab-cooling unit of Mobarakeh Steel Complex in Iran. The plan should give an hourly decline in water consumption during a one-year operation period to calculate the annual reduction in water consumption of the proposed process. Recommended solutions for the conversion scheme of an existing wet cooling tower to a dry or hybrid cooling system require modeling of the slab cooling process. The curves of temperature drop in slabs are extracted in this paper by modeling the transient heat transfer of the slabs in the cooling process. This will reduce the computational volume. Then, the design and optimization of the hybrid cooling system done by the Genetic Algorithm (GA) is investigated. Accordingly, the objective function (reducing the costs of construction, operation, waste of water during the year) is chosen by single-objective method, and the modeling of the series hybrid system is done for the off-design mode during one year. The present design is for different scenarios and various savings of water consumption. The results demonstrate that if the control system is fitted with the sensitivities of the ambient temperature and also is based on the water consumption reduction and equipment design according to reliable standards, then the annual water consumption will be reduced by 88.3% (1.89 million m 3 ). The payback period will be 3.63 years for the proposed system. Highlights: Numerical modeling of slab cooling process in transient cooling. Extraction of the outlet water performance map to model the hybrid in off-design. Modeling of off design air cooler control system and wet cooling tower. An overview of hybrid system during the year based on an optimized design.